Determination of IL-10 levels in chronic pelvic pain syndrome patients - Arısan, Serdar; Kiremit, Murat Can; Ergenekon, Erbil; Çaşkurlu, Turhan (İstanbul Kültür Üniversitesi, 2008)
Chronic pelvic pain syndrome (CPPS) is very common pathology that is characterized by pain in the perineum, pelvis, supra pubic area, or the external genitalia, with variable degrees of voiding or ejaculatory disturbance. The etiology of disorder is controversial with groups postulating infections, autoimmune, inflammatory and neuromascular mechanism. CPPS is the most commonurologic diagnosisin men younger than 50 years and the third most common urologic diagnosis in men older than 50 years after benign prostate hyperplasia and prostate cancer. Although high incidence rate, the etiology and pathophysiology of the disease are still poor.
Keywords: CPPS; cytokines; IL-10; prostatitis; prostatit; sitokinler